Pseudoangiomatous stromal hyperplasia (PASH) in a 14-year-old girl: a case report - Mallqui Mejía, Mirela (2021)
Pseudoangiomatous stromal hyperplasia (PASH) occurs between 12 and 75 years of age, being prevalent in the reproductive age. Its etiology is unknown. They are characterized by being large, deforming, unilateral and are diagnosed by ultrasound and histology. In adolescents, early surveillance, diagnosis and management is important in order to avoid radical surgeries that cause large scars, deformity and breast asymmetry, which have repercussions on the behavior and emotional state of the patients. Breast tumors are generally benign in adolescence, but their diagnosis in this age group is worrisome for the family and the patient. We present the case of a 14-year-old adolescent who underwent a submammary approach, preserving breast symmetry.